Hubungan Tingkat Nyeri Dan Kualitas Tidur Dengan Pemulihan Luka Pasien Pasca Operasi Open Reduction Internal Fixation RSUD Kanjuruhan Kabupaten Malang - DENNIS, DENNIS; MARSAID, MARSAID; SUPONO, SUPONO; SULASTYAWATI, SULASTYAWATI (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Objective: To determine the relationship between pain level and sleep quality with wound healing in postoperative ORIF patients. Methods: This study used a descriptive correlational design with a sample of 39 postoperative ORIF patients selected purposively. Participants were conscious, cooperative, had no history of diabetes, and were aged between 13–50 years. Instruments used to collect data included questionnaires on pain level, sleep quality, and wound healing. Results: Spearman Rank correlation test results showed a p-value of 0.000 (p < 0.05) with an R value of -0.772, indicating a strong relationship between pain level and wound healing after ORIF surgery. Additionally, a p-value of 0.000 (p < 0.05) with an R value of -0.789 indicated a fairly strong relationship between sleep quality and wound healing after ORIF surgery. Conclusion: There is a relationship between pain level and sleep quality with wound healing after ORIF surgery.